2012
DOI: 10.3109/09546634.2012.697988
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pediatric molluscum contagiosum with 10% potassium hydroxide solution

Abstract: Even though 10% KOH solution is associated with some local side effects, it is a safe, effective, inexpensive and noninvasive alternative treatment of MC in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…Erythema (33.3%), pruritus (22.2%), desquamation (18.5%), contact allergic (5.5%), and irritant dermatitis (5.5%) were also noted, but their frequency was not statistically significant. Burning sensation or stinging during application was the most common side effect of KOH in previous studies, similar to this study, 7,9,14,20 while others have also noted erythema and crusting, 20 hyperpigmentation, 10,17 and hypopigmentation. 12, 13 Short reported both stinging (20%) and hyperpigmentation (20%) as the most common side effects.…”
Section: Side Effects Of Therapiessupporting
confidence: 89%
See 3 more Smart Citations
“…Erythema (33.3%), pruritus (22.2%), desquamation (18.5%), contact allergic (5.5%), and irritant dermatitis (5.5%) were also noted, but their frequency was not statistically significant. Burning sensation or stinging during application was the most common side effect of KOH in previous studies, similar to this study, 7,9,14,20 while others have also noted erythema and crusting, 20 hyperpigmentation, 10,17 and hypopigmentation. 12, 13 Short reported both stinging (20%) and hyperpigmentation (20%) as the most common side effects.…”
Section: Side Effects Of Therapiessupporting
confidence: 89%
“…In other work where skin phototypes were not specified, only one of the three hypopigmentation conditions persisted. 17 Permanent hypopigmentation as a complication of KOH treatment is considered as the most important and undesired side effect in dark skinned Sudanese children evaluated in this study.…”
Section: Side Effects Of Therapiesmentioning
confidence: 88%
See 2 more Smart Citations
“…Recently, some studies have demonstrated the effectiveness of potassium hydroxide (KOH), in various concentrations of 5%, 15% and 20% for MC treatment (2)(3)(4)(5). However, there is no study comparing KOH treatment with cryotherapy.…”
Section: Introductionmentioning
confidence: 99%